HOW IS THE IMPLEMENTATION OF HALAL SELF DECLAIRE CERTIFICATION IN MICRO AND SMALL ENTERPRISES IN SURABAYA? - Aristyanto, Erwan; Sarwo Edi , Agus; Asj’ari, Fachrudy (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
This research aims to explore, analyze, and evaluate the implementation of halal certification for micro and small businesses through BPJPH (Indonesian Halal Certification Agency) and to understand how this certification process functions for these businesses in Surabaya from an Islamic economic perspective. Conducted as part of the Wijaya Putra University's Higher Education Research Strategic Plan for 2020–2024 in the field of Managing Innovation and creative Industry, this study utilizes a descriptive qualitative method. Data collection involved observation, interviews, and note-taking, followed by analysis stages including data collection, reduction, presentation, conclusion, and verification. The findings indicate that the BPJPH halal certification process for micro and small businesses in Surabaya in 2023, particularly for food products, involves several stages from online registration to certification approval after inspections and a Fatwa Commission hearing. From an Islamic economic standpoint, halal certification applies ethical principles such as aqidah, Siddiq, and Amanah, emphasizing the significance of halal food, assurance, security, and consumer protection for both consumers and business operators.